PENGARUH KEDALAMAN MUKA AIR TANAH TERHADAP LILIT BATANG KARET CLON PB260 DAN SIFAT KIMIA TANAH GAMBUT DI KEBUN MERANTI RAPP RIAU - Aries Sukariawan; Abdul Rauf; Arief Setiawan Sutanto; Bolot Santoso (Jurnal Pertanian Tropik, 2015)
Study to evaluate the effect of the depth of water table in peatlands of the PB260 rubber girthimmature plants (age 2-3 years) and chemical properties of peat soil has been carried out inMeranti Estate RAPP Kampar Estuary Pangkalan Kerinci District of Riau in December 2013.The research used a descriptive method with measuring water table depth in selected plots with girthmeasurements of planting rubber trees planted in 2010 and 2011. At two sample plots (representingthe shallowest water level and water level deep) dug each soil profile to the investigation anddecision soil samples. Soil samples were analyzed at the Laboratory of BPTP North Sumatra. Theresults showed that the water table in peatlands deeper, reaching 88.6 cm girth will decrease thegrowth of young rubber trees. Rubber immature plants age 2 years who has the best girth growth ingroundwater at a depth of 29.6 cm deep and 3 years old trunk circumference rubber girth bestgrowth at 65.3 cm water table. The water table is within reach mean 88.6 cm cause fasterdecomposition of peat soil is characterized by C/N ratio of lower and lower quality (fertility) peatsoils with lower ash content, K-exchangeable, Mg-exchangeable, P-available, and P-total.